2022
DOI: 10.3389/fpls.2022.849477
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Methyl Jasmonate Application Improved Physio-Biochemical Attributes, Yield, Quality, and Cadmium Tolerance in Fragrant Rice

Abstract: Cadmium (Cd) has detrimental effects on crop plants, whereas, jasmonates (JAs) play a vital role in abiotic stress tolerance in plants. The present study investigated the effects of exogenous application of methyl jasmonate (MeJa) on the physio-biochemical attributes, yield, and quality of two fragrant rice cultivars, i.e., Xiangyaxiangzhan and Meixiangzhan-2 under Cd stress. The experiment was comprised of four treatments, i.e., CK, control (normal conditions); Cd: 100 mg Cd kg–1 of soil; MeJa: exogenous appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…To date, numerous studies have demonstrated that the productivity of fragrant rice can be regulated through the application of various PGRs. For instance, Kanu et al 34 found that fragrant rice yield could be significantly increased by 13.4-17.6% for both experimental cultivars when uniformly sprayed with 20 mM L −1 MeJA at vegetative and reproductive stages. Jiang et al 35 also discovered that low levels of melatonin spraying could alleviate heavy metal toxicity and promote fragrant rice yield.…”
Section: Discussionmentioning
confidence: 98%
“…To date, numerous studies have demonstrated that the productivity of fragrant rice can be regulated through the application of various PGRs. For instance, Kanu et al 34 found that fragrant rice yield could be significantly increased by 13.4-17.6% for both experimental cultivars when uniformly sprayed with 20 mM L −1 MeJA at vegetative and reproductive stages. Jiang et al 35 also discovered that low levels of melatonin spraying could alleviate heavy metal toxicity and promote fragrant rice yield.…”
Section: Discussionmentioning
confidence: 98%
“… However, it has been found that foliar application of jasmonic acid, at the time of grain filling, on young seedlings of fragrant rice cultivars increased 2-AP and other volatiles . Similarly, the exogenous application of methyl jasmonate resulted in substantial improvements in yield and quality of fragrant rice under Cd toxicity . Paclobutrazol is widely recognized as an effective regulator of plant development, and the foliar application of paclobutrazol was proven efficient in improving the aroma of fragrant rice, grain quality, and yield .…”
Section: Advancement In Agro-management Practices To Improve the Arom...mentioning
confidence: 99%
“…83 Similarly, the exogenous application of methyl jasmonate resulted in substantial improvements in yield and quality of fragrant rice under Cd toxicity. 84 Paclobutrazol is widely recognized as an effective regulator of plant development, and the foliar application of paclobutrazol was proven efficient in improving the aroma of fragrant rice, grain quality, and yield. 85 Similarly, the foliar application of procyanidins (a polyphenolic compound with multiple properties), and epoxiconazole (a triazole compound) also enhanced the biosynthesis of 2-AP in aromatic rice.…”
Section: Macro/micronutrientsmentioning
confidence: 99%